Performance of elite women's singles badminton players: The influence of left-handed players - Zhang, Y.; Leng, B. (Journal of Human Kinetics, 2024)
The purpose of the study was to analyze the influence of left-handed athletes on the opponent (right-handed players) of elite badminton women's singles. The study selected a total of 40 women's singles matches played by elite female players: twenty matches (42 games, n = 42) were played between left-handed and right-handed players and twenty matches (44 games, n = 44) were played between two right-handed players. There were significant (p < 0.05) differences in hitting positions, techniques, routes and landing points. No significant (p > 0.05) differences were found in scores per game and frequency distribution of rally outcomes. In conclusion, the details of technical and tactical application were different in two game forms, the main impact of the left-handed player on the opponent's (right-handed player) game was a decrease in the opponent's stroke in the overhead, an increase in the number of drives, predominance of small slashes and a decrease in big slashes.